A Violência contra a mulher na percepção dos/das representantes da Rede de Atendimento à mulher em situação de violência na região CRAJUBAR. - Duarte, Ana Teresa (2019)
The aim of this study is to analyze the discourses on domestic and family violence against women of the representatives of the Crajubar region's network of care for women in situations of domestic violence, as well as to understand their perceptions of the biopolicies for dealing with this problem and how these biopolicies have been developing in the region. To this end, five representatives of this network were interviewed, namely: the deputy of the Crato Women's Police Station, the judge of the Juazeiro do Norte Domestic and Family Violence Court, a social worker from the Crato Women's Reference Centre, another social worker from the Juazeiro do Norte Women's Reference Centre and the Barbalha civil police chief. The instrument used to collect the data was a semi-structured interview, which was recorded and transcribed in accordance with the stipulations of the ethics committee. It was found that the interviewees perceive the Crajubar region as a place marked by high rates of domestic violence against women and attribute the main cause of gender inequalities, especially this problem, to macho culture. In relation to the biopolicies of confrontation, especially the Maria da Penha Law and the Feminicide Law, they consider these to be significant advances in the fight against violence against women, but they did point out significant challenges in terms of their development in the region.